Respostas

2013-09-21T18:23:40-03:00
a) 3.(x+4) - 6=2x+7
3x+12-6 = 2x+7
3x - 2x = 7+6-12
x = 13-12
x = 1

b)3x-10=5x+7
-10-7 = 5x-3x
-17 = 2x
x = 17/2


c)4.(2x-5) - 2.(x-8)=7x+1
8x-20-2x+16 = 7x+1
8x-2x-7x = 1+20-16
-x = -5.(-1)
x = 5


d)(x+3) + x  = 3       
  --------   ----   -----
      4        2      1                OBS: Tirando o mmc:

x+3+2x = 12
------------------
         4                                OBS: Eliminando o 4 temos: 
x+3+2x = 12
x+2x = 12-3
3x = 9
x = 9/3
x = 3

e) (x-1) - (2x+3) = (x+6) 
   --------   ---------   --------    
       
2          5           1                    OBS: tirando o mmc:

5x-5-4x+6 = 10x+60
-----------------------------
              10                          OBS: cortando o 10:
5x-5-4x+6 = 10x+60
5x-4x-10x = 60+5-6
-9x = 59(-1)
9x = -59
x = -59/9

4 4 4
2013-09-21T19:58:45-03:00
A)3x + 12 -6=2x+7
3x-2x=7+6+12
x=25

b) 3x-10=5x+7
3x-5x=7+10
-2x=17 (-1)
2x=-17
x= -17/2

c) 8x - 20 -2x +16 + 1
8x -2x -7x =1-16+20
-x = -5 (-1)
x=5


2 5 2